Impostor syndrome and academic hardiness: Investigating the impact on academic anxiety students - Firjatullah, Firjatullah; Ramadhani, Ayunda (Psychology, Evaluation, and Technology in Educational Research, 2024)
Academic life serves as a process for students to develop their abilities; however, in reality, not all students can optimize their potential. This is often related to internal factors such as emotions, feelings, and perceptions. This study aims to examine the influence of impostor syndrome tendencies and academic hardiness on academic anxiety. The research method employed is quantitative. The subjects of this study were 205 students from Mulawarman University in Samarinda, selected using purposive sampling. Data were collected using scales measuring academic anxiety, impostor syndrome, and academic hardiness. The data analysis technique used was multiple linear regression, with data analyzed using the Statistical Package for Social Science (SPSS) version 26.0 for Windows. The results of the study indicate that (1) there is a significant influence of impostor syndrome and academic resilience on academic anxiety, with an F-value of 43.279 > F-table of 3.23 and p = 0.000 < 0.05, contributing 30% of the variance; (2) there is a significant positive influence of impostor syndrome on academic anxiety, with a beta coefficient (β) = 0.459, t-value = 7.186, and p = 0.000 (p < 0.05); and (3) there is a significant negative influence of academic hardiness on academic anxiety, with a beta coefficient (β) = -0.171, t-value = -2.676, and p = 0.008 (p < 0.05).a coefficient beta (β) value of 0.363, t value = 2.407, and p = 0.021 (p < 0.05); (3) there is a significant negative influence of academic hardiness on academic anxiety with a coefficient beta (β) value of -0.472, t value = -3.127, and p = 0.003 (p < 0.05). The study finds that impostor syndrome and academic hardiness significantly influence academic anxiety, with impostor syndrome showing a positive impact and academic hardiness showing a negative impact.